ANALYSIS OF CHARACTER EDUCATION IN THE BOOK 'PROJEK PENGUATAN PROFIL PELAJAR PANCASILA' BY FERA ATMAWATI AND ITS UTILIZATION AS TEACHING MATERIAL IN THE NEGOTIATION TEXT SUBJECT FOR GRADE X IN HIGH SCHOOL - Maula, Roudhotul; Efendi, Irfan; Apriyanto, Ade (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
The author's concern about numerous cases involving adolescents in the surrounding environment serves as a reference for guiding the implementation of character education in high school or equivalent level education units. This consideration is crucial as part of an effort to prepare future generations, ensuring that students play a positive role in the future. The study seeks to identify and describe the character education values present in the Projek Penguatan Profil Pelajar Pancasila book, and its utilization as teaching materials on class x negotiation text material in High School. This research adopts a descriptive qualitative approach, with the primary variable being the content of the project book strengthening the student profile of Pancasila. The instruments employed in this research include both main and additional tools. The primary instrument is the researcher, while documentation guidelines and questionnaires serve as additional instruments. The research findings reveal the implementation of 17 character education values in the P5 book by Fera Atmawati. Subsequently, these findings are utilized as alternative teaching materials in the form of negotiation text modules for grade X students. The preparation of teaching modules undergoes validation by three experts, resulting in materials deemed effective and suitable for use. The teaching materials derived from this study contribute as an addition to the references for the few independent curriculum-based teaching modules currently needed by educators.